Peran Teknologi dalam Meningkatkan Manajemen Sumber Daya Manusia di Era Digital: Studi Kasus di SD Mathla’ul Anwar - Irfieh, Fauzia; Supendi, Pepen (BISMA : Business and Management Journal, 2024)
The application of technology in human resource management (HRM) is becoming increasingly important in the digital era, especially in the education sector. Digital transformation offers opportunities to improve the efficiency, transparency and quality of educator and school administration management. This article aims to analyze the role of technology in improving HR management at SD Mathla'ul Anwar, an educational institution that has integrated technology in various managerial aspects. This research uses a qualitative approach with a case study method, through interviews, observation, and documentation of managerial practices at Mathla'ul Anwar Elementary School. The results showed that technology has had a positive impact in various aspects of HR management, including recruitment, performance management, training, and communication between staff. However, there are challenges related to technical training and technology adoption among diverse staff. This article concludes that technology plays an important role in improving HRM in educational institutions, but more structured implementation and ongoing training are needed to maximize the potential of technology